Performance, Rumen Fluid pH, and Blood Metabolites of Lambs Fed on Whole or Ground Barley Grain - A Al-Lataifeh, Fatima; Obeidat, Belal S.; Ata, Mysaa (Jordan Journal of Agricultural Sciences, 2024)
The objective of this study was to assess the effect of feeding whole or ground barley grain on Awassi lambs. Twenty-six lambs (17.5 ± 1.28 kg) were randomly assigned to one of two treatments (13 lambs/treatment) on whole or ground barley grain. Lambs were housed individually and fed twice daily for 47 days. Initial body weight (BW) was not different when the experiment was started, as well as for the BW at the end of the experiment. At the same time, total weight gain (TWG) and the average daily gain (ADG) were significantly higher for lambs fed a diet containing ground barley grain than lambs fed a diet containing whole barley grain. The digestibility of dry matter, crude protein, neutral detergent fiber, and acid detergent fiber was greater in ground barley than in whole barley treatment. Nitrogen intake and nitrogen in the urine were similar in both lamb groups. At the same time, fecal N was greater in the group of lambs fed whole barley grain in their diet, but less amount and percentage of N retained in the body for the same group of lambs (whole grain). Blood Urea N was not affected by the dietary treatment, while blood glucose was higher in lambs fed ground barley grain compared to lambs fed a diet containing whole barley grain. In conclusion, feeding ground barley contained diet had a significant improvement in intake, digestibility, and N retention, without any negative effects on ruminal pH.